Wer ist dieser Jesus? 1700 Jahre nach Nizäa von Jesus reden - Schwarzweller-Madl, Gabriele (Münchener theologische Zeitschrift, 2025)
The Council of Nicaea became necessary when the unity of Christians was in danger of breaking apart over the question of how the divinity and humanity of Jesus Christ relate to one another, and the need for clarification could no longer be ignored. In formulating a doctrinal definition, the council drew on terminology from Greek philosophy - using terms which, as attempts from different centuries have shown, challenge every era to infuse them with fresh meaning. At the heart of the issue lies the existential significance of faith in Jesus as the Son of God and the cultivation of a living relationship with him. In this light, an examination of art serves as an argument for simplifying the language used to speak about Jesus, supported by examples from theology and the New Testament.